Ag Incorporated MoO3 Thin Films and Fabrication of Ag/MoO3/p-Si Structured Photodiode - Lavanya, G.; Sivanandan , N. (International Journal of Membrane Science and Technology, 2023)
MoO3 have been widely investigated for their applications ranging from electronics to energy storage. Orthorhombic structured MoO3 thin films were prepared on a glass substrate. The Ag doped materials to add the MoO3 in different concentrations (1%, 3%, 5%) at Wt% with MoO3 precursor and synthesis was done using the spray pyrolysis method. X-ray diffraction revealed the incorporation of Ag in the MoO3 orthorhombic structure. FE-SEM images showed more dispersive and rod shapes than Agi-doped MoO3 and pure MoO3 respectively. The jet nebulizer spray pyrolysis technique for fabrication of n-Ag: MoO3/p-Si photodiodes makes it suitable for good response photo-detecting applications.